Desenvolvimento e validação de método analítico para quantificação de impurezas orgânicas de dipirona sódica monoidratada por cromatografia líquida de alta performance (HPLC) - Machado, Patrícia Vieira (2020)
Dipyrone is an analgesic, antipyretic, spasmolytic and broad antiinflammatory use in Latin America, banned by regulatory agencies of reference due to the risk of agranulocytosis and other blood dyscrasias. To ensure the use of a drug is necessary to control the quality and stability of samples and their organic impurities. Thus, an analytical method capable of separating and quantifying the organic impurities of Dipirone was developed and validated. The objective of this work was to evaluate the behavior of Dipirone against decomposition conditions (acid, basic, oxidative hydrolysis, metal ions, temperature, humidity and photolysis), in order to evaluate the decomposition of the active and the separation of possible organic impurities, either. degradation or impurities already present in the sample. For this a method was developed and validated to make this evaluation with sensitivity, precision and accuracy. Linearity was determined at concentrations of 2.55 µg.mL-1 to 51 µg.mL-1 for impurity C and Dipyrone and 2.55 µg.mL-1 at 15.3 µg.mL-1 for impurity E. Validation was performed in gradient mode consisting of monobasic sodium phosphate buffer, pH 7.0 and methanol, using 150 x 4.6 mm (5 μm) reverse phase C18 column with detection at 254 nm. The analytical method obtained impurity retention times of approximately 12 minutes for impurity A, 16.9 minutes for impurity E, 20 minutes for Dipyrone, 22.3 minutes for impurity B, 25.6 minutes for impurity C and 27.7 minutes for impurity D, showing a resolution greater than 1.5 and optimum separation. It also presents sensitivity for analytes at low concentration, not limit of detection and quantification at 2.55 µg.mL-1, accuracy, precision and robustness for the organic impurities tested.